Հայրենական Մեծ Պատերազմում արցախահայության մասնակցության դրվագները (կուրսկի ճակատամարտի օրինակով) 9-րդ դասարանցիների հայրենասիրության դաստիարակման գործում - Կասյան, Ա. Ա.
Для армянского народа XX век сыграл существенную роль в воспитании подрастающего поколения в духе патриотизма. Во время Великой Отечественной войны в борьбе против фашизма арцахское армянство проявило отвагу и стойкость духа. Воспитанное на их примере поколение в годы Арцахской войны ничем не уступило своим предшественникам. Родную землю защитили по заветам отцов и дедов. The 20th century had a great role in the patriotic upbringing of the younger generation. During the Great Patriotic war fighting against the fashism people of Artsakh showed immense courage and strenght. Following their sample our people didn't fall behind their ancestors, during the Artsakh struggle. They protected their matherland according to the traditions of the older generation.
Keywords: Պատմության դասավանդման մեթոդիկա